Manipulación de residuos sólidos municipales y su efecto en la salud de los trabajadores de la planta de compostaje. Belén 2022 - Peña Peña, Vieri (2022)
The thesis was developed with the purpose of identifying the effects of bioaerosols produced by the handling and recovery of organic waste on the health of workers at the composting plant of the Belén District Municipality. It is a quantitative, observational, descriptive, analytical and transversal research, with a relational, non-experimental level. The sample consisted of 100 percent (20) of the recovery plant workers. The results show that they tend to be organic waste that facilitates handling and the recovery process through composting. The workers acknowledge that they handle hazardous waste, they do not have full personal protective equipment. They report receiving daily induction in proper management with a simple sanitation practice, but they do not practice it properly, putting the safety and health of workers at risk. Regarding the occurrence of illnesses, the majority of the workers report not having suffered any illness, but also, a significant minority reports having suffered any illness. The diseases that occur most frequently are allergic reactions and those with a lower incidence are eye irritation, gastritis, respiratory problems, fever, all of them mainly due to the presence of bioaerosols from handling and recovery. of organic waste. The results of the Spearmam Rho Correlation statistic for the hypothesis test report that there is a significant and indirect relationship with a very good degree of relationship. That is, when there is a greater handling of organic waste, it is related to a lower state of health of the workers. Therefore, as p < 0.05, the alternate hypothesis (H1) is accepted, that is, the handling of organic waste affects the health of the recovery plant workers.